Crossing Frontiers in Tackling Pathways of Biological Invasions - Essl, Franz; Bacher, Sven; Blackburn, Tim M.; Booy, Olaf; Brundu, Giuseppe; Brunel, Sarah; Cardoso, Ana Cristina; Eschen, René; Gallardo, Belinda; Galil, Bella S.; García-Berthou, Emili; Genovesi, Piero; et al. (My University, 2015)
Substantial progress has been made in understanding how pathways underlie and mediate biological invasions. However, key features of their role in invasions remain poorly understood, available knowledge is widely scattered, and major frontiers in research and management are insufficiently characterized. We review the state of the art, highlight recent advances, identify pitfalls and constraints, and discuss major challenges in four broad fields of pathway research and management: pathway classification, application of pathway information, management response, and management impact. We present approaches to describe and quantify pathway attributes (e.g., spatiotemporal changes, proxies of introduction effort, environmental and socioeconomic contexts) and how they interact with species traits and regional characteristics. We also provide recommendations for a research agenda with particular focus on emerging (or neglected) research questions and present new analytical tools in the context of pathway research and management.
Keywords: Alien species; Impact; Management; Propagule pressure; Temporal trends